A Sistem Informasi Penilaian Kinerja Karyawan Pada Rumah Sakit Mitra Delima - Aditama, Rizky; Anita, Anita; Cahyadiana, Windarini (J-INTECH (Journal of Information and Technology), 2022)
Mitra Delima General Hospital is a public health service institution located in Bululawang Malang. One of the efforts made to maintain employee competence is the implementation of performance appraisal which is carried out every year, namely two months before the work contract expires. This performance appraisal is at the same time a mechanism for determining the extension or termination of an employee's work contract. The large number of employees and the stages that must be carried out as well as the large number of personnel involved in the appraisal process lead to delays in scheduling and delays in the period of employee work contracts. Therefore the purpose of this study is to build an information system that can help the staffing department to detect employees who must be scheduled for performance appraisal, assign personnel to carry out the assessment and inform employees and officers of the schedule and results of work assessments so that performance appraisals can be carried out appropriately. time and more efficiently. The system built is web based using PHP scripts and the CodeIgnater framework and Mys sql as the DBMS. The system that has been built has passed the trial phase using blackbox testing and each feature has the function required so that it is expected to be able to schedule performance appraisals on time and avoid unnecessary delays in the work contract period.